Women's exercise identity increases after a 16-week exercise RCT and is linked to behavior maintenance at follow-up. (May 2021) - Gillman, Arielle S.; Stevens, Courtney J.; Bryan, Angela D.
Abstract: Background: Regular exercise is critical for disease prevention, but adherence to public health guidelines is poor. Exercise identity is purported to be associated with exercise behavior maintenance, but the extant literature is largely cross-sectional and of low/modest quality. Purpose: To examine change in exercise identity after completion of a supervised exercise intervention, as well as associations between change in exercise identity and exercise maintenance at 6-months follow-up. Methods: N = 276 insufficiently physically active women were randomized to a 16-week, supervised exercise training intervention with 4 conditions fully crossed on intensity (vigorous/moderate) and duration (long/short). Exercise identity was measured pre- and post-intervention and assessments of exercise motivation and behavior frequency were collected at 6-months post-intervention follow-up. Results: On average, participants experienced a statistically significant change in exercise identity over the course of the intervention, t (128) = 7.94, p < .001, but identity change scores did not differ across training conditions, p = .91. Identity change was significantly positively related to changes in other theory-informed, motivation-based determinants of exercise, and predicted an additional 16.17 min of exercise per week, on average, at follow-up, b = 16.76, t (103) = 2.30, p = .023. Conclusions: Participants experienced increased self-identification with exercise after 16-weeks of training, but training volume did not influence the amount of identity change. As expected, greater change in exercise identity was associated with higher levels of exercise behavior at 6-months post-intervention follow-up (ClinicalTrials.gov number NCT02032628 ). Highlights: Previously-inactive women who completed a 16-week exercise intervention increased their "exercise identity" over time. Increases in exercise identity weren't related to the amount or intensity of exercise completed. Women whose exercise identity increased more were more likely to report exercising more 6 months after the intervention.